(untitled) (Research, Society and Development, 2020)
The Atraumatic Restorative Treatment (ART) was originated with the intention of healing the need for dental treatment for poor communities. With the development of the technique there has been an expansion of its use both in public health and in private practices. Through a review of the literature, the objective of this work is to integrate information about the history, evolution, advantages and disadvantages, as well as to increase the knowledge of dentists so that they can perform with more confidence. ART is based on the philosophy of minimal intervention, its use is plausible in several situations, both in public and private services, since the technique preserves healthy tissues and reduces more invasive procedures such as endodontics and exodontia. There is a need for professionals to increase their knowledge of the technique.